Stress-Related Pre-Seismic Water Radon Concentration Variations in the Panjin Observation Well, China (1994–2020) - Zhou, Zhihua; Tian, Lei; Zhao, Jing; Wang, Haiyan; Liu, Jianguang (Frontiers in Earth Science, 2020)
Continuous observation data from a period of 26 years show that water radon concentrations in the Panjin observation well document pre-seismic anomalies prior to earthquakes of 4.8 ≤ M ≤ 7 within a radius of 300 km. Among these earthquakes, two distinct groups with different water radon concentration anomalies and anomaly mechanisms are apparent. The abnormal characteristics of water radon concentrations clearly reflect the processes of stress change, while Cl- concentration, Ca2+ concentration, Mg2+ concentration, and escaping gas flow only document part of these processes. According to Global Positioning System (GPS) main strain rate fields and area strain rate fields, the change in anomalous behavior coincides with the 2011 Great Tohoku M 9.1 earthquake. This event caused the stress state of the study area, located in eastern China, to change from a relative compressive stress state to a tensile state, and may be the main reason for the change in the precursory characteristics of water radon concentrations (from increasing to decreasing prior to earthquakes). Regardless, water radon concentration in the well remains a good pre-seismic indicator for earthquakes of M ≥ 4.8. In the near future (~50–100 years), water radon anomalies in the Panjin observation well prior to earthquakes of M ≥ 4.8 will most likely manifest as a V-shaped concentration change. Helium and neon isotopic compositions of gas samples from the Panjin observation well show that the present relatively high levels of water radon concentrations are normal and not an earthquake precursor.